CREOLIZED TEXTS AS A MEANS OF DEVELOPING LINGUISTIC COMPETENCE OF STUDENTS WITH NON-LINGUISTIC SPECIALTIES - Rajabova Svetlana Mikhailovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The relevance of using creolized texts in foreign language teaching lies in the need to expand the content and teaching tools due to the limitless information capabilities of these materials. Currently, foreign language teaching methodologists do not deny the methodological potential of polycode texts, as they are an integral part of everyday life, thereby motivating students to study a foreign language. However, in modern  methodological  literature,  there  is  a  lack  of  practical recommendations  for building a teaching system based on them. The purpose of this article is to evaluate the effectiveness  of  creolized  texts  as  a  means  of  developing  linguistic  competence  in students majoring in non-linguistic specialties. The results of the study, obtained using descriptive  statistics,  indicate  a  moderate  advantage  of  using  creolized  texts  in developing  lexical  and  grammatical  skills  in  students  majoring  in  non-linguistic specialties  and the  feasibility  of  using  these  types of  texts in  developing linguistic competence.